Paclitaxel Increases High Voltage-Dependent Calcium Channel Current in Dorsal Root Ganglion Neurons of the Rat - Kazuyoshi Kawakami; Terumasa Chiba; Nobuyuki Katagiri; Maya Saduka; Kenji Abe; Iku Utsunomiya; Toshihiro Hama; Kyoji Taguchi (Elsevier, 2012)
Peripheral neuropathic pain is a serious side effect of paclitaxel treatment. However, the mechanism of this paclitaxel-induced neuropathic pain is unknown. In this study, we investigated the effects of paclitaxel on the voltage-dependent calcium channel (VDCC) current in rat dorsal root ganglion (DRG) neurons using the whole-cell patch clamp technique. Behavioral assessment using von Frey filament stimuli showed that 2 and 4 mg/kg paclitaxel treatment induced mechanical allodynia/hyperalgesia. Paclitaxel-induced mechanical hyperalgesia was significantly inhibited by gabapentin (100 mg/kg). Using the patch clamp method, we observed that paclitaxel (4 mg/kg) treatment significantly increased the VDCC current in small- and medium-diameter DRG neurons. Moreover, paclitaxel-induced increase in the VDCC current in medium-diameter DRG neurons was completely inhibited by 10 and 100 μM gabapentin. Similar effects in small-diameter DRG neurons were only seen with 100 μM gabapentin. Western blotting revealed that paclitaxel increased protein levels of the VDCC subunit α2δ-1 (Cavα2δ-1) in DRG neurons. Immunohistochemistry showed that paclitaxel treatment increased Cavα2δ-1 protein expression in DRG neurons. Thus, paclitaxel treatment increases the VDCC current in small- and medium-diameter DRG neurons and upregulates Cavα2δ-1. The antihyperalgesic action of gabapentin may be due to inhibition of paclitaxel-induced increases in the VDCC current in DRG neurons. Keywords:: paclitaxel, voltage-dependent calcium channel current, dorsal root ganglion, gabapentin, peripheral neuropathy